Preserving Indonesia's Unity Through The Law Based On Bhineka Tunggal Ika - Soeleman Djaiz Baranyanan; Muhammad Irham; Iqbal Taufik; Hendrik Salmon; Sherlock Halmes Lekipiouw (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Based on positive law, which applies in Indonesia,decentralization has "chosen" to give up some of itsauthority to autonomous regions. The delegated authority is very broad, because in Law Number. 23 of2014 uses a residual system when determining what is the authority of local governments. With the residualsystem, the central authorities have been clearly defined in advance, while the rest are autonomous regions.Therefore, authority in the health sector has become an autonomous regional government authority, becausethat authority is not determined as the authority of the central government. On the one hand this benefits thelocal government, because by using its authority, the regional government can regulate the health sectoraccording to its aspirations and capabilities. This research was approached in terms of legal science, bothat the dogmatic level, legal theory, and legal philosophy.In this study also used a normative legal approach orlibrary law, namely legal research conducted by examining library materials or secondary data.Normative legal research or literature includes research on semantic law, research on the degree of vertical andhorizontal synchronization, comparison of law and history of law. Research on legal principles is carriedout by interpreting the legal norms formulated in laws and regulations relating to local government inIndonesia. Based on this research study, it can be concluded that in terms of law and policy as well as thescope of authority of regional governments that support regional autonomy in the health sector, it is still unclearand inconsistent in the description of the functions and authority of regional governments in the health sector